Senescence‐associated lncRNAs: senescence‐associated long noncoding RNAs. Issue 5 (14th July 2013) - Abdelmohsen, Kotb; Panda, Amaresh; Kang, Min‐Ju; Xu, Jason; Selimyan, Roza; Yoon, Je‐Hyun; Martindale, Jennifer L.; De, Supriyo; Wood, William H.; Becker, Kevin G.; Gorospe, Myriam
Summary Noncoding RNAs include small transcripts, such as microRNAs and piwi‐interacting RNAs, and a wide range of long noncoding RNAs (lncRNAs). Although many lncRNAs have been identified, only a small number of lncRNAs have been characterized functionally. Here, we sought to identify lncRNAs differentially expressed during replicative senescence. We compared lncRNAs expressed in proliferating, early‐passage, 'young' human diploid WI‐38 fibroblasts [population doubling (PDL) 20] with those expressed in senescent, late‐passage, 'old' fibroblasts (PDL 52) by RNA sequencing (RNA‐Seq). Numerous transcripts in all lncRNA groups (antisense lncRNAs, pseudogene‐encoded lncRNAs, previously described lncRNAs and novel lncRNAs) were validated using reverse transcription (RT) and real‐time, quantitative (q)PCR. Among the novel senescence‐associated lncRNAs (SAL‐RNAs) showing lower abundance in senescent cells, SAL‐RNA1 (XLOC_023166) was found to delay senescence, because reducing SAL‐RNA1 levels enhanced the appearance of phenotypic traits of senescence, including an enlarged morphology, positive β‐galactosidase activity, and heightened p53 levels. Our results reveal that the expression of known and novel lncRNAs changes with senescence and suggests that SAL‐RNAs play direct regulatory roles in this important cellular process.